2021
DOI: 10.1038/s41416-021-01270-8
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring transcriptional regulators Ref-1 and STAT3 as therapeutic targets in malignant peripheral nerve sheath tumours

Abstract: Background MPNST is a rare soft-tissue sarcoma that can arise from patients with NF1. Existing chemotherapeutic and targeted agents have been unsuccessful in MPNST treatment, and recent findings implicate STAT3 and HIF1-α in driving MPNST. The DNA-binding and transcriptional activity of both STAT3 and HIF1-α is regulated by Redox factor-1 (Ref-1) redox function. A first-generation Ref-1 inhibitor, APX3330, is being tested in cancer clinical trials and could be applied to MPNST. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…Together, our gene expression findings indicate that APE1 coordinates and is involved in most of the steps of BER; alterations in its cellular level impact other important genes in the BER pathway [ 36 ]. This contrasts with what has been observed in cancer studies [ 24 , 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Together, our gene expression findings indicate that APE1 coordinates and is involved in most of the steps of BER; alterations in its cellular level impact other important genes in the BER pathway [ 36 ]. This contrasts with what has been observed in cancer studies [ 24 , 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…APE1/Ref-1′s role in DNA repair, RNA quality control, miRNA metabolism and redox activation of transcription factors NF-κB, HIF-1α, STAT3, AP-1 and p53 has suggested that it may be a therapeutic target for many cancers [ 15 , 17 , 64 ]. Increased expression of APE1/Ref-1 is associated with cancer progression, angiogenesis and resistance to therapy in many cancers, including cancers of the pancreas, bladder, colon, prostate, lung, breast, liver, ovary, bone, malignant peripheral nerve-sheath tumors (MPNST), sarcomas and many more [ 15 , 17 , 26 , 36 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Pharmacologically inhibiting the redox function of APE1/Ref-1 may be beneficial for the treatment of various cancers, as the inhibition of APE1/Ref-1 has been associated with enhanced colorectal cancer tumor regression in preclinical studies and enhanced promyelocytic leukemia response to treatment [ 15 , 38 , 64 ].…”
Section: Targeting Ape1/ref-1 As a Therapeutic Approachmentioning
confidence: 99%
“…Inhibitors of DNA repair proteins have widely been studied alone or in conjunction with radiotherapy to enhance tumor suppression. For instance, the inhibition of the DNA base excision repair (BER) protein apurinic/apyrimidinic endonuclease, APE1, has been shown to suppress growth of several cancers ( 33 , 34 ). Similarly, overexpression of APE1 has been linked to radioresistance ( 35 , 36 ), and suppression has been shown to enhance cancer cells to RT ( 37 ).…”
Section: How Does Radiation Work: the Biologic Effects Of Radiationmentioning
confidence: 99%